Concentration fluctuations in the early stages of LLPS and partial dissolution of melt-memory in broadly distributed ethylene copolymers. (18th July 2018) - Chen, Xuejian; López-Barrón, Carlos; Zeng, Yiming; Alamo, Rufina G.
Abstract: The mechanism of liquid-liquid phase separation (LLPS) is investigated in a random ethylene 1-hexene copolymer (E/H) with a broad comonomer content distribution. SANS measurements were first carried out using the original resin with deuterium added via direct isotope exchange to preserve the original branching distribution. Upon lowering the melt temperature, the upshift of SANS profile observed only below a critical scattering vector is consistent with the signature of nucleation and growth during LLPS in the metastable region. Differences in branching distribution between the original broad resin and a broad multi-components blend of narrow E/H copolymers studied previously, result in slower LLPS dynamics in the former that has a more continuous change of comonomer content between molecules. Time-resolved light scattering and light transmittance measurements in the metastable region of the broad resin, reveal the nucleation and growth stages of LLPS. Dissolution of crystalline melt-memory, associated with an inversion of the crystallization rate with decreasing the temperature of the initial melt, is found to occur mainly within the LLPS induction period and is associated with concentration fluctuations prior to the LLPS nucleation step. The typical sea-island morphology associated with LLPS via nucleation and growth is observed under bright-field optical microscopy after one-day annealing in the metastable region. Graphical abstract: Dissolution of melt-memory in broadly distributed LLDPEs during the Induction Period of Liquid-Liquid Phase Separation. Image 1 Highlights: Melts of broadly distributed random ethylene copolymers undergo LLPS via nucleation and growth, in the metastable region, as demonstrated via SALS. The onset of LLPS is identified by DSC as an inversion of the re-crystallization temperature observed on cooling from decreasing melt temperatures. A more continuous distribution of the content of comonomer display slower LLPS kinetics than analogs with a more discontinuous distribution. Concentration fluctuations in the early stages of LLPS dissolve partially the melt-memory from the initial crystallites.